Chlorhexidine and proanthocyanidin enhance the long-term bond strength of resin-based endodontic sealer - Thaís Fantinato Trindade; Ana Flávia Simões Barbosa; Larissa Moreira Spinola de Castro-Raucci; Yara Teresinha Correa Silva-Sousa; Vivian Colucci; Walter Raucci-Neto (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of this study was to evaluate the effects of proanthocyanidin (PA) and chlorhexidine (CHX) on the bond strength (BS), failure pattern, and resin-dentin interface morphology of the endodontic sealers EndoREZ and AH Plus after 24 h and 6 months of water storage. A total of 120 prepared bovine roots were divided into six groups: AH Plus, CHX+AH Plus, PA+AH Plus, EndoREZ, CHX+EndoREZ, and PA+EndoREZ. Dentin was treated for 1 or 5 min with 2% CHX or 15% PA, respectively. Roots were filled and stored in water for 24 h or 6 months (n = 10). Root slices were subjected to push-out test and scanning electron microscopy (SEM). Data were compared using two-way ANOVA and student's t-test (α = 5%). BS decreased over time for AH Plus and untreated EndoREZ (p < 0.05). At 24 h, AH Plus had higher BS than EndoREZ (p < 0.001), with no differences among treatments for both sealers (p > 0.05). At 6 months, EndoREZ had higher BS values for CHX and PA than control (p < 0.05). AH Plus had higher BS than EndoREZ (p < 0.001), while with CHX or PA, similar BS was observed in both sealers (p > 0.05). Cohesive and mixed failures were observed in all groups. SEM revealed sealer tags in the root dentin. In conclusion, BS decreased with time and AH Plus had higher BS than EndoREZ in untreated dentin; however, CHX or PA enhanced long-term BS of EndoREZ. Overall, dentin treatment affected failure pattern and resin-dentin interface morphology, particularly for EndoREZ.